Komposisi Botani dan Produksi Hijauan Pakan serta Kapasitas Tampung Padang Rumput Alam di Desa Praipaha: Botanical Composition and Forage Production and Capacity of Natural Grasslands in Praipaha Village - Maria Oktavia Biso; Herayanti P. Nastiti; Stefanus Tany Temu (Universitas Nusa Cendana, 2024)
This study aims to collect information on forage composition, forage production, and capacity of natural grasslands inPraipah Village, which is located in Ngaha Ori Angu District, East Sumba Regency. Forage for natural pastures can befound in the natural meadows of Praipah Village, which is a place of study material. The research was conducted usinga survey approach, in addition to direct observation and measurements in the field. The